If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 11)(x + 5) = 2 Reorder the terms: (11 + x)(x + 5) = 2 Reorder the terms: (11 + x)(5 + x) = 2 Multiply (11 + x) * (5 + x) (11(5 + x) + x(5 + x)) = 2 ((5 * 11 + x * 11) + x(5 + x)) = 2 ((55 + 11x) + x(5 + x)) = 2 (55 + 11x + (5 * x + x * x)) = 2 (55 + 11x + (5x + x2)) = 2 Combine like terms: 11x + 5x = 16x (55 + 16x + x2) = 2 Solving 55 + 16x + x2 = 2 Solving for variable 'x'. Reorder the terms: 55 + -2 + 16x + x2 = 2 + -2 Combine like terms: 55 + -2 = 53 53 + 16x + x2 = 2 + -2 Combine like terms: 2 + -2 = 0 53 + 16x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-53' to each side of the equation. 53 + 16x + -53 + x2 = 0 + -53 Reorder the terms: 53 + -53 + 16x + x2 = 0 + -53 Combine like terms: 53 + -53 = 0 0 + 16x + x2 = 0 + -53 16x + x2 = 0 + -53 Combine like terms: 0 + -53 = -53 16x + x2 = -53 The x term is 16x. Take half its coefficient (8). Square it (64) and add it to both sides. Add '64' to each side of the equation. 16x + 64 + x2 = -53 + 64 Reorder the terms: 64 + 16x + x2 = -53 + 64 Combine like terms: -53 + 64 = 11 64 + 16x + x2 = 11 Factor a perfect square on the left side: (x + 8)(x + 8) = 11 Calculate the square root of the right side: 3.31662479 Break this problem into two subproblems by setting (x + 8) equal to 3.31662479 and -3.31662479.Subproblem 1
x + 8 = 3.31662479 Simplifying x + 8 = 3.31662479 Reorder the terms: 8 + x = 3.31662479 Solving 8 + x = 3.31662479 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 3.31662479 + -8 Combine like terms: 8 + -8 = 0 0 + x = 3.31662479 + -8 x = 3.31662479 + -8 Combine like terms: 3.31662479 + -8 = -4.68337521 x = -4.68337521 Simplifying x = -4.68337521Subproblem 2
x + 8 = -3.31662479 Simplifying x + 8 = -3.31662479 Reorder the terms: 8 + x = -3.31662479 Solving 8 + x = -3.31662479 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = -3.31662479 + -8 Combine like terms: 8 + -8 = 0 0 + x = -3.31662479 + -8 x = -3.31662479 + -8 Combine like terms: -3.31662479 + -8 = -11.31662479 x = -11.31662479 Simplifying x = -11.31662479Solution
The solution to the problem is based on the solutions from the subproblems. x = {-4.68337521, -11.31662479}
| 3x^6-6x^8= | | N*0.8=3.5 | | 3x+45=12x+9 | | 13T-7+10T=2 | | 3x-x+6y-4x-7= | | -4(-11b-19)=-20+20b | | 22+6b=19 | | 7-7x-3=-41+3x-15 | | 11b-12=b+33 | | 13T-7+10T= | | -10x-14x= | | -4(-3z-5)=(10z+8)-2z | | -6(x-4)=8-4x | | x(x)-22x=-96 | | -16+4x=-5(1-3x) | | 11b-12=6b+44 | | F(x)=7x^3-19x^2-6x | | -19.4c=7.36-18.6c | | 25t+6=2 | | -2(8+p)=-50 | | 13+-7+10=2 | | -5k+6k= | | 17.44+4.3p=p+6.88 | | 2x^2+4y^2=25 | | (12+2x)(20+2x)=468 | | 8(5n-2)=-7(1-7n) | | 7(12-y)-y=0 | | 8xy+3yz-7xz-8xy= | | -8[-8x-6]=6x-22 | | 39x=18 | | 19.4-2.42-7.1m=-13.4m-16.41 | | 4(m-2)+15=21 |